AMBIGUITAS PENGATURAN KEADAAN BAHAYA DALAM SISTEM KETATANEGARAAN INDONESIA (Faculty of Law, Maranatha Christian University, 2019)
This article aims to analysis state of emergency rules in Indonesia. it contains practical power during state of emergency. A state of emergency is a situation that threaten the life and nation and caused political instability. A state of emergency regulated within article 12 constitution of the republic of Indonesia gives extraordinary power to the President to act against the emergency situation. Besides constitution, state of emergency also regulated by several acts (Perppu 23/1959 UU 24/2007 and UU 7/2012) and each act has different concept of state of emergency. Based on Perppu 23/1959, there are five kinds of situation called state of emergency (rebellion, riot, civil war, disaster and war). Furthermore, UU 24/2007 and UU 7/2012 regulate disaster, riot and civil war separetely and give special authority to the local government (Governor, Bupati and Mayor) proclaiming state of emergency. Besides special authority, these acts ( UU 24/2007 and (UU 7/2012) regulate different concept of how long state of emergency applicable. The result, these different concepts affect several acts such as UU 31/1999 that regulates the death pinalty for those person who doing corruption during state of emergency and local government has no right to proclaim state of emergency based on UU 23/2014 that separates authority between central and local government. State of emergency related to security and defence issues and according to UU 23/2014 security and defence issues are the part of central government authority.